2018
DOI: 10.1038/s41467-018-06721-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient carrier multiplication in CsPbI3 perovskite nanocrystals

Abstract: The all-inorganic perovskite nanocrystals are currently in the research spotlight owing to their physical stability and superior optical properties—these features make them interesting for optoelectronic and photovoltaic applications. Here, we report on the observation of highly efficient carrier multiplication in colloidal CsPbI3 nanocrystals prepared by a hot-injection method. The carrier multiplication process counteracts thermalization of hot carriers and as such provides the potential to increase the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 59 publications
(72 reference statements)
8
101
0
Order By: Relevance
“…For instance, Li et al demonstrated enhanced MEG with threshold down to 2.25 times of the bandgap and slope efficiency up to 75% in intermediate‐confined colloidal FAPbI 3 nanocrystals, and the efficient MEG was found to occur within 90 fs via inverse Auger process . Simultaneously, Weerd et al reported the observation of highly efficient (up to 98%) MEG or carrier multiplication in colloidal CsPbI 3 nanocrystals, with the threshold near the energy conservation limit of twice the bandgap . Such efficient MEG process observed in perovskite nanocrystals may lead to the realization of next generation of solar cells that can overcome the Shockley–Queisser limit.…”
Section: Excitons and Related Phenomena In Metal Halide Perovskitesmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, Li et al demonstrated enhanced MEG with threshold down to 2.25 times of the bandgap and slope efficiency up to 75% in intermediate‐confined colloidal FAPbI 3 nanocrystals, and the efficient MEG was found to occur within 90 fs via inverse Auger process . Simultaneously, Weerd et al reported the observation of highly efficient (up to 98%) MEG or carrier multiplication in colloidal CsPbI 3 nanocrystals, with the threshold near the energy conservation limit of twice the bandgap . Such efficient MEG process observed in perovskite nanocrystals may lead to the realization of next generation of solar cells that can overcome the Shockley–Queisser limit.…”
Section: Excitons and Related Phenomena In Metal Halide Perovskitesmentioning
confidence: 98%
“…Many other studies also revealed the ultrafast behaviors of localized excitons, biexcitons, trions and multiple exciton generation in perovskites by transient techniques. He et al reported that the radiative recombination of the photogenerated species in solution‐processed methylammonium–lead–halide films was dominated by excitons weakly localized in band tail states, under the excitation level close to the working regime of solar cells, and such exciton localization effect was found to be general in several solution‐process perovskite films .…”
Section: Excitons and Related Phenomena In Metal Halide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cubic structure of CsPbI 3 also can be stabilized by the colloidal quantum dot (QD) method, because the enlarging surface energy inhibits the phase transition . In addition, on the basis of the multiple exciton generation effects, the narrow bandgap colloidal QDs will exceed the single‐junction Shockley–Queisser solar efficiency limit to achieve higher theoretical efficiency …”
Section: Introductionmentioning
confidence: 99%
“… 22 The slow cooling rates are beneficial for MEG to occur, and investigations have reported on high efficiencies hereof in perovskite QDs. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%